Concept and Nature of Fulfillment in the Law of Iran and Shiite Jurisprudence - morteza shahbazi nia; kianoush razaghi (پژوهش‌نامه حقوق اسلامی, 2012)
Payment of debts by the third parties is a phenomenon frequently occurring in the realm of law and financial relations of people among themselves. The third party occasionally does not have any legal or religious responsibility from the promisor for fulfillment of obligation. Then other motives such as benevolence, or satisfaction of some joint interests with the debtor stimulates him into this act. However, sometimes although the third party is not the principal and actual debtor, he is obliged to pay the debt to the debtor according to the law. The fulfillment of obligation by the third party is essentially a permitted act except in cases in which the personal payment of the promisor is stipulated. The criterion towards recognition of the stipulation of the personal fulfillment of the promisor is its explicit mention in the contract, or the prevailing custom and usage, or the social interests following the personal fulfillment of obligations. It seems that the right of the reference of the third party to the debtor does not follow the traditional rule mentioned in Article 267 of Civil Law any longer. It follows a new rule based on which -if a particular law has not issued the permission of the fulfillment of debt by the third party and then his referring to the debtor, the third party has not been authorized by the debtor, and the payment of debt by him is not considered an example of undue and unjust fulfillment – the third party has the right of referring to the debtor on condition that he is authorized by the debtor towards payment of  the debt. However, if the third party has fulfilled the obligation based on one of the three above mentioned cases, he has the right of referring to the debtor even without being authorized by him.